LoC-SERS toward clinical application: Quantification of antibiotics in human urine samples - Hidi, I. J.; Jahn, M.; Weber, K.; Pletz, M. W.; Bocklitz, T. W.; Cialla-May, D.; Popp, Jürgen (Progress in Biomedical Optics and Imaging - Proceedings of SPIE, 2017)
The determination of the concentration of xenobiotics in biological matrix followed by the change of the prescribing procedure plays a major role in the transition from general to personalized medicine. For this contribution, human urine samples collected from healthy volunteers and from patients having urinary tract infection were used as biological matrix to assess the potential and limitation of LoC-SERS to detected levofloxacin and nitroxoline. The determination of both antibiotics at clinically relevant concentrations, 1.38 mM ± 0.68 mM for levofloxacin and 10-40 μM for nitroxoline, will be presented. For quantification purposes the standard addition method is combined with LoC-SERS.
CRIS-Team Scopus Importer:2023-04-20